Delivering an Effective Speech - James E. Dyer (EDIS)
WC085, a 5-page fact sheet by James E. Dyer, describes how to present a speech effectively by overcoming nerves, developing stage presence, refining vocal qualities, maximizing power of expression, making eye contact, and using presentation aids. Includes references. Published by the UF Department of Agricultural Education and Communication, December 2008.